Design and Implementation of a Multi-port Solid State Transformer for Flexible Der Integration - (:unkn) unknown (My University, 2017)
Conventional power system includes four major sections, bulk generation, transmission network, distribution network, and loads. The main converter in the conventional electric grid is the low-frequency passive transformer providing galvanic isolation and voltage regulation for various voltage zones. In this configuration, small-scale renewable energy resources are generally connected to the power system at low voltage zones or inside microgrids. Recent developments in the design of power electronic elements with higher voltage and power ratings and medium/high frequency enable making use of solid state transformer at different voltage levels in the distribution system and microgrid design. In this work, the concept of a Multi-Port Solid State Transformer (MPSST) for distribution network application is introduced. MPSST provides a compact, integrated and galvanically isolated multi-port node for microgrid and distribution applications and reduces the number and size of the converters in the concept of efficient smart distribution systems. A new architecture for distribution systems integrating distributed generation (DG) at different voltage zones using MPSST is proposed, studied and simulated. The developed concept interconnects different voltage types and levels using one compact converter with a centralized control logic. In addition, a general method is developed and mathematically analyzed to provide active and reactive power support using the local alternative power sources through MPSST. MPSST is a combination of high-frequency power electronic converters and a multi-winding high-frequency transformer. The total size of the MPSST is dramatically smaller than the conventional transformers with the same voltage and power rating. MPSST also enables online measurement and data collection and active control of the parameters at all connected ports. A two-layer control technique, which is a combination of duty cycle control and a modified phase shift control is used to regulate the voltage and power flow of the different ports. Since the converter has several independent and dependent variables, a transfer matrix between variables of the converter is calculated and used in system control. Finally, the implementation process of the converter including, component selection, modeling, software development, and transformer design is presented and the first prototype of the MPSST is developed and tested in the lab. Chapter five includes the hardware test results and the discussion and comparison of the results with the design expectations.
Keywords: High Frequency Transformer; Multi-port Sst; Power Electronic; Solid State Transformer; SST